Real-time fluorescence imaging for visualization and drug uptake prediction during drug delivery by thermosensitive liposomes. (1st January 2019) - Motamarry, Anjan; Negussie, Ayele H.; Rossmann, Christian; Small, James; Wolfe, A. Marissa; Wood, Bradford J.; Haemmerich, Dieter
Abstract: Objective: Thermosensitive liposomal doxorubicin (TSL–Dox) is a promising stimuli-responsive nanoparticle drug delivery system that rapidly releases the contained drug in response to hyperthermia (HT) (>40 °C). Combined with localized heating, TSL–Dox allows highly localized delivery. The goals of this study were to demonstrate that real-time fluorescence imaging can visualize drug uptake during delivery, and can predict tumor drug uptake. Methods: Nude mice carrying subcutaneous tumors (Lewis lung carcinoma) were anesthetized and injected with TSL–Dox (5 mg/kg dose). Localized HT was induced by heating tumors for 15, 30 or 60 min via a custom-designed HT probe placed superficially at the tumor location. In vivo fluorescence imaging (excitation 523 nm, emission 610 nm) was performed before, during, and for 5 min following HT. After imaging, tumors were extracted, drug uptake was quantified by high-performance liquid chromatography, and correlated with in vivo fluorescence. Plasma samples were obtained before and after HT to measure TSL–Dox pharmacokinetics. Results: Local drug uptake could be visualized in real-time during HT. Compared to unheated control tumors, fluorescence of heated tumors increased by 4.6-fold (15 min HT), 9.3-fold (30 min HT), and 13.2-fold (60 min HT). HT duration predicted tumor drug uptake ( p  = .02), with tumor drug concentrations of 4.2 ± 1.3 µg/g (no HT), 7.1 ± 5.9 µg/g (15 min HT), 14.1 ± 6.7 µg/g (30 min HT) and 21.4 ± 12.6 µg/g (60 min HT). There was good correlation ( R 2  = 0.67) between fluorescence of the tumor region and tumor drug uptake. Conclusions: Real-time in vivo fluorescence imaging can visualize drug uptake during delivery, and can predict tumor drug uptake.